A Simple Surface-Complex Model (SCM) for Metal Ion Adsorption Mechanism - Sen, Tushar (World Academy of Science, Engineering and Technology, 2012)
Surface Complexation models (SCMs) have been shown to be capable of describing metal ion adsorption processes onto oxides and mineral surfaces. These adsorption models assume thatmetal ions form complexes with surface functional groups in a manner similar to metal-ligand association in a solution phase. A simple double layer model based on surface complexationmechanism has been developed to describe the experimental observations of Ni (II) adsorption on oxides. It has been found from the model analysis as well as experimentally that the adsorption Ni((II) on iron oxide increases with solution pH, initial metal ion concentration and loading rate respectively. The developed model gives satisfactory agreements with our experimental value.